Geomatics Technology Spatio-Temporal Dynamics of Flooding in Samarinda City Based on Instagram Posts - M. Firzy Handika Saputra; Yaskinul Anwar; Yulian Widya Saputra; Iya Setyasih; H. Rahmadi (Poltanesa, 2025)
Flooding is a frequent disaster in Samarinda City, Indonesia that causes significant disruptions and losses. This study aimed to analyze the spatial and temporal patterns of flooding in Samarinda using Instagram posts as a data source. A total of 987 public posts related to flooding were collected and used to map the affected areas and identify temporal dynamics. A spatial analysis was conducted using GIS software, and the results were validated using field observations, official flood-prone area maps, and daily rainfall data. The findings showed that most flooding points were concentrated in low-lying residential areas adjacent to rivers, with increasing severity during intense rainfall. Spatial-temporal analysis revealed that high rainfall, overflow of the Karang Mumus River, and overflow of the Mahakam River were the leading causes of flooding. Over the five years, there was a significant temporal decline in the flood frequency, primarily driven by a reduction in rainfall-related events. The spatial patterns also shifted, with the Mahakam River becoming a more significant threat to the riparian areas. Instagram has emerged as a valuable dynamic geospatial data source for flood monitoring, providing timely updates and enabling the visualization of flood events. This study highlights the potential of integrating social media data into official monitoring systems to improve spatial resolution and response speed in flood management. These findings contribute to the development of social media-based flood monitoring methods and provide insights for strengthening flood mitigation planning and disaster risk reduction strategies in Samarinda City.